Registered nurse case managers' work experiences with a person-centered collaborative healthcare model: an interview study - Markus Hjelm; Anna Andersson; Venera Ujkani; Ewa Kazimiera Andersson (BMC, 2024)
Abstract Background Multimorbidity is increasingly acknowledged as a significant health concern, particularly among older individuals. It is associated with a decline in quality of life and psychosocial well-being as well as an increased risk of being referred to multiple healthcare providers, including more frequent admissions to emergency departments. Person-centered care interventions tailored to individuals with multimorbidity have shown promising results in improving patient outcomes. Research is needed to explore how work practices within integrated care models are experienced from Registered Nurse Case Managers' (RNCMs) perspective to identify areas of improvement. Therefore, the aim of this study was to describe RNCMs' work experience with a person-centered collaborative healthcare model (PCCHCM). Methods This study used an inductive design. The data were collected through individual interviews with 11 RNCMs and analyzed using qualitative content analysis. Results Data analysis resulted in four generic categories: 'Being a detective, 'Being a mediator', 'Being a partner', and 'Being a facilitator of development' which formed the basis of the main category 'Tailoring healthcare, and social services to safeguard the patient's best.' The findings showed that RNCMs strive to investigate, identify, and assess older persons' needs for coordinated care. They worked closely with patients and their relatives to engage them in informed decision-making and to implement those decisions in a personalized agreement that served as the foundation for the care and social services provided. Additionally, the RNCMs acted as facilitators of the development of the PCCHCM, improving collaboration with other healthcare professionals and enhancing the possibility of securing the best care for the patient. Conclusions The results of this study demonstrated that RNCMs tailor healthcare and social services to provide care in various situations, adhering to person-centered care principles and continuity of care. The findings underline the importance of implementing integrated care models that consider the unique characteristics of each care context and adapt different case managers' roles based on the patient's individual needs as well as on the specific needs of the local setting. More research is needed from the patients' and their relatives' perspectives to deepen the understanding of the PCCHCM concerning its ability to provide involvement, security, and coordination of care.